In Vitro And In Vivo Liposomes Formulation Studies Of Orthosiphon Stamineus Extract For Lung Cancer - Baharetha, Hussein Mahfoudh Saeed (2018)
In this study, anti-angiogenic and anti-tumour potencies of the standardized 50% ethanol extract of Orthosiphon stamineus leaves (O.S extract) were assessed towards human lung cancer in vitro and in vivo. Liposomal drug delivery system was developed from the O.S extract to improve bioavailability, efficacy, stability and safety profiles of the O.S extract. Three formulation was developed based on the extract : phospholipid ratio, phospholipid and cholesterol content. NP2, which is a formulation consisting of 1:1 extract to phosphatidylcholine ratio with 20% cholesterol, showed optimum entrapment efficiency, integrity, stability and efficacy of the liposomes. Liposomes were characterized qualitatively and quantitatively using light, TEM and SEM microscopy (which shows intact formation of nano-spherical shaped vesicles with mostly smooth surface and completely closed bilayer membrane), zetasizer and zeta potential (which reports anionic nano-vesicles with dynamic diameter 125-132 nm). NP2 shown significantly better release properties of the bioactive compounds and good stability profile than the O.S extract for six months stability studies (P≤0.05) at 30ºC or below. The O.S extract and the liposomes partially inhibited proliferation of human lung adenocarcinoma (A549) and human normal endothelial cells (EA.hy926), and revealed potent anti-angiogenic potency as in ex vivo assay of rat aortic ring. TEM analysis of A549 cells shows obvious apoptotic morphological alterations, with indication of the cellular uptake of the liposomes. It also inhibited in vitro colonization, cells invasion and cell migration in a dose–time dependent manner. Protein array and dual-luciferase studies show overexpression of various apoptotic-regulating proteins, including TGF-β and MAPK/ERK, TRAILR-1, Bid, Bax, caspase 3, IGFBP-1 and IGFBP-5; and down-regulation of some other pathways, such as WNT, Bcl-2, cIAP-2, livin, IGFBP-3, IGFBP-6 and IGF-1SR. The O.S extract and NP2 inhibited EA.hy926 cells colonization, migration and tube formation, and also down-regulated the expression of VEGF and HIF-1α indicating anti-angiogenic activity. In vivo studies reveal potent anti-tumour activity of the O.S extract and the NP2 liposome formulation towards human lung cancer in xenograft tumour model and decreased VEGF expression. Pharmacokinetic studies show that the liposomes increased oral bioavailability and improved pharmacokinetic profile. Acute and sub-acute toxicity studies reveal good margin of safety for the NP2 formulation. The liposomes (NP2) show significantly better efficiencies with enhanced bioavailability and stability compared to the non-formulated O.S extract (E) (P≤0.05). All-in-all, the results of this study indicates that the O.S extract has potent anti-tumour activity towards lung carcinoma and the NP2 liposome formulation improves its anti-tumour efficacy.